LOGIKA MATEMATIKA, DIALEKTIKA DAN TEKNIK PENGAMBILAN SIMPULAN - Imamul Muttakhidah (INSPIRAMATIKA, 2015)
Mathematics need another knowledge to be perfect for himself, therefore, enables mathematics to develop broadly. The presentation should be able to get rid of the contradiction between theory and reality. Likewise logic as the science of thinking/reasoning will continue to experience growth.Classical logic or formal logic have only spiked on a symbol. If the logic problem changed its character in the problems of everyday life, and trying to achieve a more complex understanding of the dialectics run. Until it is concluded that the proper and appropriate character issues. Criticism or disagreement is intended to enrich the material to think about the logic.